Key Influencing Factors Affecting Academic Performance: An Exploratory Study of Undergraduate IT Students of UTAS-Shinas in Sultanate of Oman - Al Kalbani, Salama Said Sulaiyam; Al Mamari, Bushra Said Obaid; Villar, Redjie (International Journal of Asian Education, 2026)
The issue of academic performance has garnered serious attention in higher education due to its consequences for both the individual learner and the institution. This study employs exploratory analysis research design to investigate the factors which influence the student’s academic performance. Data were collected from first year to third year undergraduate IT students for a sample of (N=150) at the University of Technology and Applied Sciences (UTAS)-Shinas, Sultanate of Oman who were under academic probation using a structured questionnaire. The study mainly focuses on investigating the key factors that led to their poor academic performance. Findings reveal that IT students who are in probation are aware of the academic policy of the university and are satisfied with the academic support services provided by the university generally. However, the results indicated that some academic support services should be enhanced. Results further reveal that first-year participants were less satisfied with their time management skills as compared to higher years. Moreover, intensive requirement of the courses, difficulty of the courses content and lack of basic skills were the academic factors that led to their poor academic performance. The result also shows that personal factors like exhaustion, lack of motivation and passion and inability to manage stress influenced a student’s academic performance. The university needs to collect students’ feedback on the services offered to better cater to their needs. A periodic review of the university’ current practices for the students is required to help them maintain satisfactory academic standing.